Mechanical properties and DIC analyses of CAD/CAM materials - Porto, Thiago [UNESP]; Roperto, Renato; Akkus, Anna; Akkus, Ozan; Porto-Neto, Sizenando [UNESP]; Teich, Sorin; Lang, Lisa; Campos, Edson [UNESP] (Medicina Oral, S.L., 2016)
Background: This study compared two well-known computer-aided-design/computer-aided-manufactured (CAD/ CAM) blocks (Paradigm MZ100 [3M ESPE] and Vitablocs Mark II [Vita] in terms of fracture toughness (Kic), index of brittleness (BI) and stress/strain distributions. Material and Methods: Three-point bending test was used to calculate the fracture toughness, and the relationship between the Kic and the Vickers hardness was used to calculate the index of brittleness. Additionally, digital image correlation (DIC) was used to analyze the stress/strain distribution on both materials. Results: The values for fracture toughness obtained under three-point bending were 1.87Pa√m (±0.69) for Paradigm MZ100 and 1.18Pa√m (±0.17) for Vitablocs Mark II. For the index of brittleness, the values for Paradigm and Vitablocs were 73.13μm-1/2 (±30.72) and 550.22μm-1/2 (±82.46). One-way ANOVA was performed to find differences (α=0.05) and detected deviation between the stress/strain distributions on both materials. Conclusions: Both CAD/CAM materials tested presented similar fracture toughness, but, different strain/stress distributions. Both materials may perform similarly when used in CAD/CAM restorations.
Keywords: CAD/CAM; Ceramic; Composite resin; Fracture toughness; Hybrid materials